Immigration Policies and the Ecuadorian Exodus - Bertoli, Simone (World Bank, 2013)
Ecuador recently experienced an unprecedented wave of emigration following the severe economic crisis of the late 1990s. Individual-level data for Ecuador and its two main migration destinations, Spain and the United States, are used to examine the size and skill composition of these migration flows and the role of wage differences in accounting for these features. Estimations of earnings regressions for Ecuadorians in all three countries show substantially larger income gains following migration to the United States than to Spain, with the wage differential increasing with migrants' education level. While this finding can account for the pattern of positive sorting in education toward the United States, it fails to explain why most Ecuadorians opted for Spain. The explanation for this preference appears to lie in Spain's visa waiver program for Ecuadorians. When the program was abruptly terminated, monthly inflows of Ecuadorians to Spain declined immediately.